Electrical swing adsorption on functionalized hollow fibers - Keller, Laura; Lohaus, Theresa; Abduly, Lorenz; Hadler, Greta; Wessling, Matthias (Chemical engineering journal (Lausanne, Switzerland : 1996), 2019)
[Display omitted] •Preparing two different highly absorptive hollow fibers with Joule heating properties.•Proof-of-concept module yields promising CO2 capacities.•Adequate models describe the kinetics and isotherms precisely.•Mathematical modelling proves the potential of an electrical swing adsorption process with our fibers. Temperature swing adsorption (TSA) is a favorable adsorption technique when applied for capturing CO2 but limited by long cycle times and low concentrations of the recovered adsorbate. Direct heating of the adsorbent can mitigate these drawbacks. Combined with the beneficial mass transfer of a hollow fiber geometry it offers a powerful sorption process. In this study, we combine the advantages of direct heating and the benefits of the hollow fiber geometry in electrically conducting hybrid hollow fibers. Two different solid sorbents are manufactured and characterized: polyethylenimine-impregnated silicon carbide fibers (SiC-PEI) and fibers consisting of a carbon nanotube matrix with dispersed zeolite particles (CNT-zeolite). Both fibers exhibit Joule heating properties and high adsorption capacities. The CO2 uptake, CO2 isotherms, and the kinetic behavior are examined. The maximum CO2 uptakes at 30 °C and 15 vol% CO2 are 8.3 mg/gfiber for SiC-PEI and 102.2 mg/gfiber for CNT-zeolite. A lab-scale module is designed and used to determine the CO2 capacity of a fiber bundle. The energy requirement to heat such a fiber bundle from ambient temperature to 80 °C is 3.1 J/gFiberK (SiC-PEI) and 15.8 J/gFiberK (CNT-zeolite). To investigate the suitability of the fibers for real process applicability, a mathematical model is established and simulation results are presented and discussed. The two different approaches prove to be viable options for CO2 separation. They are not limited to CO2 capture but can be expanded to other gas separation tasks.